Spike frequency adaptation in primate lateral prefrontal cortex neurons results from interplay between intrinsic properties and circuit dynamics - Nils A. Koch; Benjamin W. Corrigan; Michael Feyerabend; Roberto A. Gulli; Michelle S. Jimenez-Sosa; Mohamad Abbass; Julia K. Sunstrum; Sara Matovic; Megan Roussy; Rogelio Luna; Samuel A. Mestern; Borna Mahmoudian; et al. (Cell Reports)
Summary: Cortical neurons in brain slices display intrinsic spike frequency adaptation (I-SFA) to constant current inputs, while extracellular recordings show extrinsic SFA (E-SFA) during sustained visual stimulation. Inferring how I-SFA contributes to E-SFA during behavior is challenging due to the isolated nature of slice recordings. To address this, we recorded macaque lateral prefrontal cortex (LPFC) neurons in vivo during a visually guided saccade task and in vitro in brain slices. Broad-spiking (BS) putative pyramidal cells and narrow-spiking (NS) putative inhibitory interneurons exhibit both E-SFA and I-SFA. Developing a data-driven hybrid circuit model comprising NS model neurons receiving BS input reveals that NS model neurons exhibit longer SFA than observed in vivo; however, adding feedforward inhibition corrects this in a manner dependent on I-SFA. Identification of this circuit motif shaping E-SFA in LPFC highlights the roles of both intrinsic and network mechanisms in neural activity underlying behavior.